Estetiche della percezione - DESIDERI, FABRIZIO; Matteucci, Giovanni (Studi e saggi, 2007)
This book is a continuation of the lively debate launched in Dall'oggetto estetico all'oggetto artistico which the same editors published with Firenze University Press. The argument of the book is the organic link connecting the two thematic axes that define the ambit of aesthetics: the theory of perception and reflection on the arts. The apparent tautology of the title is intended to stress how the interpenetration of perception and work of art is structural and organic, thus calling up the theoretical urgency of this problem for an effective understanding of the dynamics of the sense of art as a "symbolic form" in which the relation between the mind and the world is embodied in an exemplary manner. The book is divided into three sections. The first presents nuclei of reflection emerging from unconventional contemporary perspectives. The second addresses various angles of the theory of perception. Finally, the third part explores several cases in which contemporary artists have tackled the link between expressive practice and the articulation of perception.